The Role of Sharanas and Anubhavamantapa in the Rise of Women - Bhimabai S Malashetti, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Women are given only a secondary role to play especially in the indian society. Right from the birth discrimination between a boy and girl is found in almost every household. Basaveshwara was probably the after Buddha to recognize and realize the individuality and rights of women and he launched a social revolution for their emancipation. The vachana movement started by Basveshwara for emancipation of women was a movement for self respect and dignity. The vachanas (sayings) of Basveshwara speak about liberty, equality, fraternity, dignity and respect which the human rights ensure and which ultimately contribute to the common good. Women were given patronage at the Anubhava mantapa among whom Akka Mahadevi received highest praise from Basavanna. There were women followers with their respective vocations. All Sharanas, including Basaveshwara, accorded mothers position to woman, we evidence of Basveshwara’s broad view of women in his treatment of his wives, and a good number of sharanes (women saints) who participated in the religious discussions at Anubhava Mantapa. Married women also took part in the movement. There were also women devotees of lower background.
Keywords: Women emancipation; Vachana movement; Life satisfaction; women position; social life; environment